Sistem Pelaporan dan Monitoring Data Limbah Pada Dinas Lingkungan Hidup dan Kebersihan Kabupaten Badung - Wijaya, Anak Agung Ngurah Mahendra; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i02.P04, 2023)
In the waste reporting process is still done manually, so the hotel is required to come to the Badung Regency Environment and Hygiene Office and then submit the report. These activities cause the reporting process to require a long duration and the progress of the report cannot be monitored by the hotel. The formulation of the problem in this study is how to report and monitor waste data from hotels quickly using the Waste Data Reporting and Monitoring System. The purpose of this research is to help hotels, especially in Badung district, in providing waste reporting quickly. In making this system, the design concept goes through the stages of data collection, Cross Functional Flowchart, Context Diagram, Level 0 Data Flow Diagram, Entity Relationship Diagram, Conceptual Database and Interface Design. And then implement it with Hypertext Preprocessor Programming (PHP), Bootstrap Framework, MySQL.